The Effect of Visual Merchandise and Store Atmosphere on Purchase Decision with Hedonic Orientation as Moderator: A study on KKV Store Surabaya - Giovani Anggasta Susanto; Michael Adiwijaya (Petra International Journal of Business Studies, 2023)
The development of the retail industry in Indonesia has been affected by the covid-19 pandemic that has entered Indonesia since 2019. To restore the situation, retail business players must find ways to increase their turnover through increased sales which can be achieved by purchasing decisions by consumers. This study examines the effect of visual merchandise and store atmosphere on purchase decisions moderated by hedonic orientation. This research uses customers of the KKV store in Surabaya as objects, and there are 110 valid samples obtained from the data collection using a questionnaire. The results showed that visual merchandise, store atmosphere, and hedonic orientation significantly affect purchase decisions. In addition, hedonic orientation as a moderator does not significantly affect purchase decisions.